Open versus minimally invasive sphincter-sparing surgery for rectal cancer: a single-center retrospective cohort study in Peru - Guevara-Jabiles, A (2022)
OBJECTIVE: The study aimed to describe and compare minimally invasive surgery (MIS) and open surgery for rectal cancer in Peru. MATERIAL AND METHODS: A retrospective single-center analysis was performed for all patients who underwent sphinctersparing surgery for non-metastatic rectal cancer at Instituto Nacional de Enfermedades Neoplásicas in Peru between January 2016 and December 2020. Clinical, perioperative, pathological, and survival outcomes were compared between both groups. A propensity score matching method was used to minimize bias. RESULTS: 162 patients were included in the final analysis. 124 had open surgery and 38 had MIS. Patients, clinical tumour, pathological characteristics, and perioperative were similar between groups after matching. Similar circumferential resection margin (CRM) with optimal quality of the mesorectum (p=1.000) but higher number of lymph nodes resected in open surgery group (p=0.741) was described. The leakage rate was slightly higher in the MIS group (p=0.358) with 10.5%, while the postoperative hospital stay was longer in the open surgery group after matching (p=0.001 OR 95% 5.2 CI: 1.8-15.6). The estimated recurrence-free survival (RFS) and overall survival (OS) at 3 years in open surgery and MIS was 71.8% (95% CI 0.58-0.89) and 70% (95% CI 0.56-0.88) (p=0.431) and 77.7% (95% CI 0.64-0.94) and 88.9% (95% CI 0.79-0.99) (p=0.5), respectively. CONCLUSIONS: Shorter postoperative hospital stay in the minimally invasive surgery group was reported. RFS, OS, and recurrence rates were similar between both groups. This approach is for non-metastatic rectal cancer in referral centers in Peru.